Long-term (2004–2015) tendencies and variabilities of tropical UTLS water vapor mixing ratio and temperature observed by AURA/MLS using multivariate regression analysis. (September 2016) - Sridharan, S.; Sandhya, M.
Abstract: Long-term variabilities and tendencies in the tropical (30°N–30°S)monthly averaged zonal mean water vapor mixing ratio (WVMR) and temperature in the upper troposphere and lower stratosphere (UTLS), obtained from the Microwave Limb Sounder (MLS) instrument onboard Earth Observing System (EOS) satellite for the period October 2004-September 2015, are studied using multivariate regression analysis. It is found that the WVMR shows a decreasing trend of 0.02–0.1 ppmv/year in WVMR below 100 hPa while the trend is positive (0.02–0.035 ppmv/year) above 100 hPa. There is no significant trend at 121 hPa. The WVMR response to solar cycle (SC) is negative below 21 hPa. However, the magnitude decreases with height from 0.13 ppmv/100 sfu(solar flux unit) at 178 hPa to 0.07 ppmv/100sfuat 26 hPa. The response of WVMR to multivariate El Niño index (MEI), which is a proxy for El Niño Southern Oscillation (ENSO), is positive at and below 100 hPa and negative above 100 hPa. It is negative at 56–46 hPa with maximum value of 0.1 ppmv/MEI at 56 hPa. Large positive (negative) quasi-biennial oscillation (QBO) in WVMR at 56–68 hPa reconstructed from the regression analysis coincide with eastward (westward) to westward (eastward) transition of QBO winds at that level. The trend in zonal mean tropical temperature is negative above 56 hPa with magnitude increasing with height. The maximum negative trend of 0.05 K/year is observed at 21–17 hPa and the trend insignificant around tropopause. The response of temperature to SC is negative in the UTLS region and to ENSO is positive below 100 hPa and mostly negative above 100 hPa. The negative response of WVMR to MEI in the stratosphere is suggested to be due to the extended cold trap of tropopause temperature during El Niño years that might have controlled the water vapor entry into the stratosphere. The WVMR response to residual vertical velocity at 70 hPa is positive in the stratosphere, whereas the temperature response is positive in the UTLS region and negative above 56 hPa. Besides, the interannual variability and the response of the WVMR to the different parameters are explained based on the response of temperature at 100 hPa (proxy for tropopause) to those parameters. Highlights: Increasing (decreasing) trend in WVMR (temperature) above 82 hPa (56 hPa). No significant trend in WVMR and temperature near tropopause (100 hPa). Low tropopause temperature and stratospheric WVMR during 50 hPa westward QBO. During El Niño, negative anomaly in tropopause temperature throughout Pacific. This explains negative response of stratospheric WVMR to El Niño.